2019
DOI: 10.4062/biomolther.2018.107
|View full text |Cite
|
Sign up to set email alerts
|

Tenovin-1 Induces Senescence and Decreases Wound-Healing Activity in Cultured Rat Primary Astrocytes

Abstract: Brain aging induces neuropsychological changes, such as decreased memory capacity, language ability, and attention; and is also associated with neurodegenerative diseases. However, most of the studies on brain aging are focused on neurons, while senescence in astrocytes has received less attention. Astrocytes constitute the majority of cell types in the brain and perform various functions in the brain such as supporting brain structures, regulating blood-brain barrier permeability, transmitter uptake and regul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 62 publications
1
11
0
Order By: Relevance
“…In addition to the morphological and molecular features of senescent cells, etoposide-treated astrocytes also showed a functional change manifested by their reduced wound-healing ability. The results are consistent with our previous reports showing a reduction of wound healing ability in senescence-induced astrocytes by tenovin-1 via changes in the expressions of sirt1 and 2 (Bang et al ., 2018). It has been reported that aged bone marrow-derived dendritic cells reveal impaired in vitro migration (Grolleau-Julius et al ., 2008) and old tenocytes and satellite cells also show migration defects (Chang et al ., 2012; Collins-Hooper et al ., 2012).…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…In addition to the morphological and molecular features of senescent cells, etoposide-treated astrocytes also showed a functional change manifested by their reduced wound-healing ability. The results are consistent with our previous reports showing a reduction of wound healing ability in senescence-induced astrocytes by tenovin-1 via changes in the expressions of sirt1 and 2 (Bang et al ., 2018). It has been reported that aged bone marrow-derived dendritic cells reveal impaired in vitro migration (Grolleau-Julius et al ., 2008) and old tenocytes and satellite cells also show migration defects (Chang et al ., 2012; Collins-Hooper et al ., 2012).…”
Section: Discussionsupporting
confidence: 94%
“…Western blot analysis was performed following a published protocol described previously (Bang et al ., 2018). Briefly, the cells were harvested with radioimmunoprecipitation assay (RIPA) buffer consisting of 2 mM EDTA, 0.1% (w/v) SDS, 50 mM Tris-HCl, 150 mM sodium chloride, 1% Triton X-100, and 1% (w/v) sodium deoxycholate.…”
Section: Methodsmentioning
confidence: 99%
“…Our results showed that late passage cultivated astrocytes exhibited functional changes manifested by decreased wound healing capacity. These results are consistent with our previous reports showing the decreased wound healing capacity in aging-induced astrocytes through tenovin-1 or etoposide treatment ( Bang et al ., 2019a , 2019b ). Old satellite cells and tenocytes show impaired migration in vitro similar to aged bone marrow-derived dendritic cells ( Grolleau-Julius et al ., 2008 ; Chang et al ., 2012 ; Collins-Hooper et al ., 2012 ).…”
Section: Discussionmentioning
confidence: 99%
“…Sprague-Dawley (SD) rats were obtained from Samtako, Inc (Gyeonggi, Korea). Astrocytes were cultured in the brain cortex of postnatal day 2 (P2) SD rats as described previously ( Bang et al ., 2019b ). Briefly, brain cortices were isolated and mechanically triturated to make single cells.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation